ISPC Commentary on the Proposal for CRP7 - October 2010 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2010)
ISPC Commentary on the Proposal for CRP 7: Climate Change, Agriculture and Food Security (Version of August 2010).